2016
DOI: 10.1111/1742-6723.12530
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study of patients' choice between public and private hospital emergency departments

Abstract: Patients who choose to attend public EDs appear to value financial concern over waiting time; those who choose to attend private EDs appear to value waiting time ahead of financial concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…He et al 1 and Shearer et al 2 found that patients value and prefer the care and expertise given in a private ED. This may be because private EDs are staffed with senior, highly trained emergency doctors (FACEMs, senior ACEM trainees and long-term experienced CMOs), who see the patients directly, rather than via a junior trainee.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al 1 and Shearer et al 2 found that patients value and prefer the care and expertise given in a private ED. This may be because private EDs are staffed with senior, highly trained emergency doctors (FACEMs, senior ACEM trainees and long-term experienced CMOs), who see the patients directly, rather than via a junior trainee.…”
Section: Introductionmentioning
confidence: 99%
“…He and colleagues provide us with a timely, novel and important piece of research, continuing the work of identifying the rationale for patient choice of a public or private facility when facing a health emergency in Australia.…”
mentioning
confidence: 99%
“…6,8 Interestingly, all but one paramedic said they presented because of the patient requesting to attend our private ED, indicating that specific direction could be the first point in the paramedics decision-making. The themes identified were not entirely surprising and align with previous Australian work exploring patients (as opposed to paramedics) reasons for choosing a private ED.…”
Section: Discussionmentioning
confidence: 99%
“…The themes identified were not entirely surprising and align with previous Australian work exploring patients (as opposed to paramedics) reasons for choosing a private ED. 6,8 Interestingly, all but one paramedic said they presented because of the patient requesting to attend our private ED, indicating that specific direction could be the first point in the paramedics decision-making. The other three factors are then likely to be modifying factors, influencing whether the paramedic felt the direction could be complied with or was appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…During normal operations, public or private EDs are chosen by patients and paramedics for a variety of reasons. Patients balance financial disincentives in private against perceptions of prolonged wait times in public . Paramedics have a default practice of delivering patients to public EDs and over‐riding this practice and taking a patient to a private ED requires active decision‐making, usually at the request of a patient, family, treating general practitioner or physician …”
Section: Introductionmentioning
confidence: 99%